2009
DOI: 10.2478/v10036-009-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-1 Gene DNA Variation Predicts Performance in Hispanic Marathon Runners

Abstract: Introduction and aim of the study: We examined the association between a DNA sequence variant in the aquaporin-1 (AQP1) gene and performance in Hispanic marathon runners. Materials and methods: DNA samples (N = 784) were obtained from apparently healthy, biologically unrelated, ethnically matched Hispanic marathon runners who participated in international level marathons in Spain and Mexico. Cases (n = 396; men= 225; women=171) finished in the top 3 rd percentile for their age and gender, while Controls (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 23 publications
6
36
1
Order By: Relevance
“…The association of the CG and CC genotypes with faster running performance is consistent with that observed by both Martínez et al (2009) and Rivera et al (2011). Martínez et al (2009) observed the C-allele at a higher frequency in Hispanic marathon runners who finished in the top 3% (n = 396; C-allele: 36%), compared to those who finished in the bottom 3% (n = 388; Callele: 30%) of their respective age and gender categories (odds ratio 1.35; 95% confidence interval 1.08-1.67; P = 0.005). Rivera et al (2011) observed that recreational long distance runners who carried a C-allele (CG or CC genotypes; n = 50) completed a …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The association of the CG and CC genotypes with faster running performance is consistent with that observed by both Martínez et al (2009) and Rivera et al (2011). Martínez et al (2009) observed the C-allele at a higher frequency in Hispanic marathon runners who finished in the top 3% (n = 396; C-allele: 36%), compared to those who finished in the bottom 3% (n = 388; Callele: 30%) of their respective age and gender categories (odds ratio 1.35; 95% confidence interval 1.08-1.67; P = 0.005). Rivera et al (2011) observed that recreational long distance runners who carried a C-allele (CG or CC genotypes; n = 50) completed a …”
Section: Discussionsupporting
confidence: 88%
“…Five hundred and four (504) The distribution of AQP1 rs1049305 genotypes in the triathletes included in this study did not differ significantly from Hardy-Weinberg equilibrium and were similar to those reported elsewhere (Fábrega et al, 2011;Martínez et al, 2009;Rivera et al, 2011). There were no genotype effects on any physiological characteristics of the triathletes, including age (P = 0.343), height (P = 0.678), body mass index (P = 0.703), pre-race serum sodium concentration (P = 0.848), post-race serum sodium concentration (P = 0.647), pre-race weight (P = 0.610) nor relative weight change during the Ironman Triathlons (P = 0.705) ( Table I) (Table I).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…During osmotic stress, such as occurs during intense exercise, AQP1 facilitates the transfer of water from the blood into the muscle, provides osmotic protection, and promotes water reabsorption. Martínez et al [51] have examined the association between AQP1 gene rs1049305 C/G polymorphism (in the 3 0 -UTR) and athletic performance in 784 Hispanic international level marathon runners. Athletes were divided into two groups: (1) cases (n ¼ 396), finished in the top third tertile for their age and gender;…”
Section: Aqp1 Rs1049305 C Allelementioning
confidence: 98%